Dynamic Rheological, Thermal, and Structural Properties of Starch from Modified Cassava Flour (MOCAF) with Two Cultivars of Cassava - Diniyah, Nurud; Iguchi, Miyuki; Nanto, Mai; Yoshino, Tomoyuki; Subagio, Achmad (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2023)
AbstractThe objectives of this study were to investigate alteration in the starch properties of modified cassava flour from two different local cassava cultivars from Indonesia at different fermentation times, provide structural information for starch molecules, and characterize the dynamic rheological and thermal properties. Resistant starch, non-resistant starch, and total starch levels in the cassava cultivars were also evaluated. Changes in the starch properties of Cimanggu and Kaspro (local cultivars of cassavas from Indonesia) were compared following different fermentation times (0, 12, and 24 hours). The properties of starch from modified cassava flour were influenced by the fermentation time, although both cassava varieties showed the same general characteristics. Their levels of resistant starch, non-resistant starch, and total starch were 33.28% to 51.74%, 20.51% to 23.72%, and 53.81% to 72.25% (g/100 g dry sample), respectively. The starch granules for the non-fermented samples were oval, polygonal, and round shapes; however, during fermentation, the starch granules became more porous and developed cracks of various sizes. The starches of both varieties showed an onset temperature between 67.85 and 70.17 °C, a peak temperature of 69.33 °C to 71.62 °C, and an end set temperature of 68.62 °C to 70.95 °C, with enthalpy values ranging from 1.25 mJ/mg to 1.74 mJ/mg. Keywords: cassava, cultivar, dynamic rheological, fermentation, modified cassava starch AbstrakTujuan dari penelitian ini adalah untuk mengetahui perubahan sifat pati tepung singkong termodifikasi dari dua varietas singkong lokal Indonesia dengan lama fermentasi yang berbeda, memberikan informasi struktur molekul pati, dan melakukan karakterisasi sifat rheologi dan termal dinamis dari pati. pati resisten, pati non-resisten, dan kadar pati total dalam varietas singkong. Perubahan sifat pati Cimanggu dan Kaspro (varietas singkong lokal Indonesia) dibandingkan setelah dilakukan fermentasi pada waktu yang berbeda (0, 12, dan 24 jam). Sifat pati dari tepung singkong termodifikasi dipengaruhi oleh lama fermentasi, meskipun kedua varietas singkong menunjukkan karakteristik umum yang sama. Kadar pati resisten, pati non-resisten, dan total pati masing-masing 33,28% – 51,74%, 20,51% – 23,72%, dan 53,81% – 72,25% (g/100 g sampel kering). Granula pati dari sampel non-fermentasi berbentuk oval, poligonal, dan bulat. Namun, selama fermentasi, granula pati menjadi lebih berpori dan mengembang dengan terdapat retakan pada berbagai ukuran. Pati dari dua varietas menunjukkan onset temperature (suhu awal) antara 67,85 °C dan 70,17 °C, suhu puncak 69,33 °C – 71,62 °C, dan suhu akhir 68,62 °C – 70,95 °C, dengan nilai entalpi berkisar dari 1,25 mJ/mg - 1.74 mJ/mg.Kata Kunci: dinamik rheologi, fermentasi, pati singkong termodifikasi, singkong, varietas